Projeto raia de fogo: aspectos populacionais da raia de fogo (Dasyatis marianae Gomes, Rosa & Gadig, 2000) e pesca de elasmobrânquios no complexo recifal do Parracho de Maracajaú - Costa, Tiego Luiz de Araújo (2011)
The species Dasyatis marianae inhabits coastal areas associated with coral reefs, considered endemic to the northeast of Brazil, occurring from the State of Maranhão to the south of Bahia. Specimens of this species are commonly sighted by divers and fishermen in the area of Maracajaú reefs, a complex reef that is part of the Environmental Protection Area of Coral Reefs (EPACR), which was developed in this study about the ecology and biology of the D. marianae, in order to characterize aspects of population structure in the area of the reef complex of Parracho de Maracajaú. We analyzed 120 specimens caught by artisanal fishing site of the size, weight, sex, stage of maturity and stomach contents. Most subjects were adult males (1.7:1) and was more abundant for rays with lengths between 25 and 29cm of LD, where females reach larger sizes, a feature common to other rays. The largest specimens were captured in the area of seagrass, which is preferred for the species. The distribution of species in the area showed an ontogenetic and sexual segregation, where the youthful occur near the beach, which is a likely area for nursery and growth of the adult females prevail in the seagrass, which apparently has a high prey availability, and Adult males are more distant, a higher proportion occurring in outlying areas, suggesting a habit more exploratory than the females. The evaluation of the reproductive system indicated 3 reproductive cycles per year, one young per pregnancy, and showed that the mature males were smaller than females. The cubs of D. marianae size at birth 12 to 15cm LD. As for diet, the species was characterized as carnivorous crustacean specialist. The performance of visual censuses in different localities allowed to evaluate the density of D. marianae in different environments of the complex. The species occurs in greater numbers in seagrass, environment very important for the conservation of the species. 100 individuals of D. marianae marked in reef complex area enrolled in a recapture rate of 3%. Some behavioral aspects were evaluated, as diurnal pattern of activity, interaction with cleaning and fish Pomacanthus paru followers as Lutjanus analis and Carangoides bartholomaei. Overall, much of the information obtained should be used for management of the species